RESPON MAHASISWA PGMI UNISMA TERHADAP PEMBELAJARAN ONLINE DI TENGAH PENYEBARAN WABAH CORONA VIRUS (COVID-19) - Muhammad Alda Wijayanto; Ika Ratih Sulistiani; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The outbreak of the corona virus has halted the implementation of learning activities. Online learning is a new breakthrough in the world of education so that learning activities can continue. This study aims to describe the response of PGMI Unisma students to online learning during the covid-19 virus outbreak. This study uses quantitative methods. The number of respondents who studied were 75 students. The results showed that the percentage of PGMI Unisma students towards learning during the pandemic was 76% agree and 24% disagree. The percentage of PGMI Unisma students towards online learning during the pandemic as much as 53% agree and 47% disagree. According to the calculation of the moment product correlation hypothesis test using SPSS 20, there is a low correlation between learning during a pandemic and online learning during a pandemic of 0.331.Keyword: Online learning, Covid-19.